The verbal reasoning test workbook unbeatable practice for verbal ability, English usage and interpretation and judgement tests - Bryon, Mike; IG Publishing (London Kogan Page, 2011)
This book will help you to prepare for these tests, offering you everything you need for a comprehensive program of self-study, including advice on what to expect on the day, English usage questions, sentence sequences and 150 warm-up questions. It includes 700 practice questions, four full-length realistic mock tests, detailed explanations of answers and interpretations of scores.
Adopt the winning approach -- 150 warm-up questions -- 150 verbal reasonings questions -- 150 English usage questions -- 100 true, false and cannot tell questions -- Four full-length realistic practice tests -- Answers, explanations and interpretations of your score.
Electronic reproduction.
Keywords: Verbal ability -- Examinations, questions, etc; Reasoning (Psychology) -- Examinations, questions, etc; Employment tests -- Examinations, questions, etc; Electronic books